A scientometric analysis of career anchor/orientation research from 1975 to 2023 - Asegid Getachew Woldeamanuel (Future Business Journal)
Abstract Career has traditionally been associated with its external dimension. However, the emergence of the concept of career anchor/orientation broadened its scope to include an internal component that encompasses the subjective desire, values and talents of individuals. The current scientometric review focused on analyzing career anchor/orientation research over the last five decades (1975–2023). The articles/documents used for analysis were searched and located from a purposely selected highly recognized databases. A total of 111 documents (articles, books, book chapters, conference proceedings) were selected for analysis. The result showed that the conceptualization of career anchor/orientation has remained stable with only some changes and emergence of few rival models. While the existing literature has provided valuable insights into the concept of career anchors, there are several gaps that need to be addressed. Future research should strive to expand the current understanding of career anchors by exploring additional career anchors, investigating their organizational implications, examining their interaction with other individual and contextual factors, and studying their manifestation in non-traditional work settings. The research in the area has shown a swinging trend with lots of ups and downs. Career anchor/orientation publications were spread over more than 24 countries. The US is ranked 1st with 28% of the total publication and is followed by the Asia continent and the UK. Africa, only represented by two countries (South Africa and Nigeria), is ranked fourth. Most of the empirical research have mainly focused on assessing the distribution of the dimensions of career anchor/orientation with few relating it with job settings and outcomes. It is recommended that career anchor/orientation scientometric analysis should be done by searching articles from more databases. More to this, as national contexts and cultural differences play a critical role in shaping career anchor/orientation of individuals it is suggested that more research needs to be done across a number of countries.